Graduates' skills and employability: the view of students from different European countries. Issue 4 (11th January 2019) - Pereira, Elisabeth T.; Vilas-Boas, Madalena; Rebelo, Cátia C.
Abstract : Purpose: In the last decade, graduates' employability has assumed a central role in scholars' concerns. This was mainly due the high rate of recent graduates' unemployment in some European countries, as well as the Bologna Process reform of the European higher education system and the new Europe Strategy 2020. The purpose of this paper, driven by the increasing need to improve graduates' skills and employability, is to identify a set of skills that students consider important to achieve success in their own field of study and another set of skills, which they perceive to lack the most. Design/methodology/approach: To achieve the main goal of this study, based on the methodology supported by literature review, a questionnaire was applied to students from five different European universities. Findings: The main results allowed the authors to infer that, on the one hand, the European students of the universities included in the study consider communication, thinking and interpersonal skills as the most important skills to get a job in their own field of study; and on the other hand, personal, interpersonal and entrepreneurial skills are the skills lacked by students. These set of skills are quite similar and even overlapping, which makes this a significant inference that needs to be accounted by higher education institutions (HEIs). Originality/value: In the research carried out in this study, with the students of five different European universities affected by the economic crisis of 2007/2008, the needed skills perceived by students to obtain employment in their own field of study were identified, along with the skills which they perceived to lack the most. The obtained findings contribute to shed light on the important issue of supporting HEIs regarding the skills that should be imparted in the curricula of their courses and workshops, in order to help the students to succeed in the current and potential competitive labour market.